2009
DOI: 10.1080/08860220902839097
|View full text |Cite
|
Sign up to set email alerts
|

Fifty Years of Balkan Endemic Nephropathy: Challenges of Study Using Epidemiological Method

Abstract: Balkan endemic nephropathy (BEN) is a chronic tubulointerstitial disease associated with urothelial cancer, which affects people living in the alluvial plains along the tributaries of the Danube River. Challenges of studying BEN using the epidemiological method are multiple. The natural history from exposure to occurrence of the disease may take many years. The early stages of BEN are not easily detectable clinically, as the disease is asymptomatic until a significant decline in function occurs, and even then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 26 publications
(25 reference statements)
1
26
0
5
Order By: Relevance
“…Worldwide, these CKDue epidemics are localised in the dry zones of agricultural societies, where the landscape is flat and the ground conditions are harsh, with little rain and prolonged dry periods and drought. Examples of somewhat similar CKDu conditions reported in other countries include Uddanam, in the agricultural belt of Andhra Pradesh [7]; unusual nephropathy, in China [8] and Nicaragua [9]; and Balkan endemic nephropathy, which affects rural villages in Serbia, Bulgaria, Romania, Croatia, and Bosnia [10,11].…”
Section: Uniqueness Of the Ckd-mfomentioning
confidence: 99%
See 1 more Smart Citation
“…Worldwide, these CKDue epidemics are localised in the dry zones of agricultural societies, where the landscape is flat and the ground conditions are harsh, with little rain and prolonged dry periods and drought. Examples of somewhat similar CKDu conditions reported in other countries include Uddanam, in the agricultural belt of Andhra Pradesh [7]; unusual nephropathy, in China [8] and Nicaragua [9]; and Balkan endemic nephropathy, which affects rural villages in Serbia, Bulgaria, Romania, Croatia, and Bosnia [10,11].…”
Section: Uniqueness Of the Ckd-mfomentioning
confidence: 99%
“…Worldwide, CKD of unknown/uncertain aetiology has been reported after chronic exposure to certain heavy metals, including arsenic, cadmium, mercury, chromium, uranium, gold, platinum, silver, thallium, and antimony, as well as fluoride [4,19,20] and agrochemicals [7][8][9][10][11]. Despite the epidemiological studies carried out over the past 40 years, other than the reported associations and correlations (except arsenic in ground-water, Bihar, India), no causative factor has been identified for CKDu across the continent.…”
Section: Postulated Causes For Ckd-mfomentioning
confidence: 99%
“…AA poisoning (31), ochratoxin, or lignites from coal field runoff, have been proposed as environmental agents that may cause BEN (reviewed in Ref. 54). Several lines of evidence, including the finding of AA-derived aristolactam-DNA adducts in kidney DNA of BEN patients, and fingerprint A:T-ϾT:A transversion mutations in the TP53 gene in urothelial tumors from BEN patients, have solidified the consensus that BEN is a form of AAN (26).…”
mentioning
confidence: 99%
“…11,12 Similarly, Balkan-endemic nephropathy, which affects people living along the tributaries of the Danube river in Europe, is now considered to be a form of aristolochic acid-related kidney disease. 13 In two studies in India partially funded by the ISN Research and Prevention Committee, no excess of heavy metals was found in the water in the Srikakulam district (MS Ravishankar, Seven hills Hospital, Mumbai, India, personal communication), while contamination of ground water used for drinking purposes with trace elements such as silica was suspected of causing CKD described in rural villages in the state of Andhra Pradesh (G. Taduri, Nizams Institute of Medical Sciences, Hyderabad, India, personal communication).…”
Section: Discussionmentioning
confidence: 99%